Pengembangan Modul Mikrobiologi Berbasis Penelitian - Pratiwi, Anggita Marta; Primiani, Cicilia Novi; Yuhanna, Wachidatul Linda (Florea : Jurnal Biologi dan Pembelajarannya, 2023)
ABSTRACTThe module is expressed as a complete learning resource package consisting of a series of learning processes. The module is also a source of teaching materials that make it easier for students to achieve learning goals. Research-based modules are needed to improve student learning outcomes. Research-based modules make students achieve the criteria for completeness. The type of research used is research and development (Research & Development) with the ADDIE approach model. The small-scale test subjects are fourth semester students of the Biology Education Study Program, PGRI Madiun University who have taken the Microbiology course. The instruments used are initial needs questionnaires, material and media validation questionnaires and small-scale test questionnaires for students. The percentage of results from the validation of material microbiologists is 80.5%, media expert validation is 91% and for small-scale tests 91%. Based on these results, it can be concluded that the mycorbiology module based on the antibacterial test of the genitry plant (Elaeocarpus sphaericus) is valid and feasible to be used as teaching material in microbiology courses.Keyword: Module, Research base, Research & Development, ADDIE